STRUCTURAL AND COMPOSITIONAL REORGANIZATION IN PERMANENT CAATINGA PLOTS: EVIDENCE OF COMPENSATORY GROWTH AND REDISTRIBUTION OF DOMINANCE BETWEEN 2022 AND 2024 (REMUNOM, 2026)
Seasonally dry tropical forests exhibit dynamics that are strongly modulated by climatic variability and water stress, factors that simultaneously influence mortality, growth, and species composition. This study evaluated structural and compositional changes in 32 permanent plots located in the Caatinga, Northeastern Brazil, by comparing forest inventories conducted in 2022 and 2024. Variations in stem density (N), basal area (G), diameter distribution, species-specific contribution to structural increment (ΔG), Bray–Curtis dissimilarity, and multivariate patterns through NMDS ordination were analyzed.A slight reduction in mean density per plot was observed, accompanied by a marked increase in basal area, indicating compensatory growth of the remaining individuals. Diameter class distribution showed a decline in the smallest class and an increase in intermediate classes, suggesting structural progression with limited recruitment during the study period. Basal area increment was concentrated in a few species, particularly Prosopis juliflora and Poincianella pyramidalis, indicating a reorganization of structural dominance. Dissimilarities were higher when based on basal area than on abundance, revealing stronger changes in biomass structure than in floristic composition. NMDS ordination revealed heterogeneous shifts among plots, suggesting locally differentiated responses.The results indicate that, during the analyzed interval, the community exhibited significant structural growth accompanied by a reorganization of dominance, a pattern consistent with recent processes described for Latin American dry forests under climatic variability.